Epilepsy and Neuroscience: Evolution and Interaction - Reynolds, Edward Henry (Frontiers in Neuroanatomy, 2020)
Neuroscience is a relatively new and fashionable word that emerged in the 1950s in several countries, including the UK, to describe a multidisciplinary clinical and laboratory approach to the study of the brain, mind, and neuropsychiatric disorders. However collaborative study of neurological and psychiatric disorders can be traced to the 17th century with roots in antiquity. I describe the evolution of our understanding of epilepsy beginning with the first detailed clinical descriptions, associated with supernatural theories, in Babylonian medicine in the second millennium BC. Interest in natural causation arose in the Greco-Roman period when it was first suggested that “the sacred disease” was a disorder of the brain. However, this theory did not take root until the 17th and 18th centuries AD when epilepsy began to be separated from other “convulsive” diseases, including hysteria. In the 19th century developments in neuropathology and our understanding of cortical localization led to the much-debated separation of idiopathic from symptomatic epilepsy which continues to influence international classifications of seizures and epilepsies. Also in the 19th century, the concept of seizures as electrical discharges in the brain evolved, reinforced in the 20th century by the discovery of the electroencephalogram. For many reasons, people with epilepsy have experienced a high incidence of cognitive and psychosocial disorders. Epilepsy, which is a global problem, has, therefore, remained a bridge between neurology and psychiatry. Furthermore, the study of epilepsy continues to shed light on brain function and other neuropsychiatric disorders.